2020
DOI: 10.21203/rs.3.rs-50023/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intranasal exposure of African green monkeys to SARS-CoV-2 results in acute phase pneumonia with shedding and lung injury still present in the early convalescence phase

Abstract: We recently reported the development of the first African green monkey (AGM) model for COVID-19 based on a combined liquid intranasal (i.n.) and intratracheal (i.t.) exposure to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Here, we followed up on this work by assessing an i.n. particle only route of exposure using the LMA mucosal atomization device (MAD). Six AGMs were infected with SARS-CoV-2; three animals were euthanized near the peak stage of virus replication (day 5) and three animals we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 24 publications
6
19
0
Order By: Relevance
“…Other recent studies have suggested rhesus macaque as potential laboratory animal model for carrying out SARS-CoV-2 studies due to viral shedding, signs and symptoms similar to humans (Yu et al 2020;Munster et al 2020;Ying et al 2020). Similar observations of infection after inoculation of virus have been reported in African green monkeys used to study COVID-19 infection (Cross et al 2020).…”
Section: Laboratory Animal Modelssupporting
confidence: 64%
See 1 more Smart Citation
“…Other recent studies have suggested rhesus macaque as potential laboratory animal model for carrying out SARS-CoV-2 studies due to viral shedding, signs and symptoms similar to humans (Yu et al 2020;Munster et al 2020;Ying et al 2020). Similar observations of infection after inoculation of virus have been reported in African green monkeys used to study COVID-19 infection (Cross et al 2020).…”
Section: Laboratory Animal Modelssupporting
confidence: 64%
“…Thus, the persons who work on wildlife are in close contact with such animals and/or work for wildlife management and are in close contact with wildlife species, should follow stringent preventive measures to avoid the spread of the virus. SARS-CoV-2 has been detected rarely from other animal species including rhesus macaques, African green monkeys and Egyptian fruit bats; this highlights the possibility of cross-species transmission of SARS-CoV-2 (Schlottau et al 2020;Yu et al 2020;Munster et al 2020;Cross et al 2020). A latest study from the Netherlands investigated on the spread of SARS-CoV-2 virus from mink back to humans working on the mink farm.…”
Section: Possible Role Of Wild Animalsmentioning
confidence: 99%
“…NHP represent a mild COVID-19 disease model that is widely used to bolster preclinical SARS-CoV-2 vaccine efficacy against upper and lower respiratory tract infection in an animal species that is more closely related to humans [49][50][51][52][53][54][55][56] . We used the African green monkey NHP model to assess COH04S1 vaccine protection against SARS-CoV-2 by 2D and 1D vaccination regimens, referred to as COH04S1-2D and COH04S1-1D, respectively.…”
Section: D and 1d Vaccination Of Nhp With Coh04s1 Stimulates Robust Antigen-specific Binding Antibodies Nab Responses And Antigen-specifimentioning
confidence: 99%
“…3B). Besides, we regarded ACE2 of Rhinolophus sinicus, Chlorocebus sabaeus, and Macaca fascicularis as permissive, and regarded Callithrix jacchus as non-permissive orthologs respectively, as published experimental evidence proved that ACE2 of R. sinicus could mediate SARS-CoV-2 entry into HeLa cells (Zhou et al, 2020), Chlorocebus sabaeus (Cross et al, 2020), and Macaca fascicularis(S. were susceptible to SARS-CoV-2 infection, and yet C. jacchus was not susceptible to SARS-CoV-2 infection(S. Lu et al, 2020).…”
Section: Classification Of Permissive and Non-permissive Ace2 Ortholomentioning
confidence: 99%